The factors influencing health wellbeing in Celcom Johor / Badrul Emran Badrul Hisham - Badrul Hisham, Badrul Emran (Faculty of Business and Management, 2018)
The purpose of this study was to identify the factors that have significant relationships and influence most on the state of health wellbeing towards Celcom employees at Celcom Southern Regional Office. The state of health wellbeing was assessed through various variables such as psychosocial work environment, physical workplace environment, work life balance and organizational culture. Demographic variables were also assessed to determine whether a relationship existed with health wellbeing. This research study is considered a quantitative research which used self-administered questionnaires as instruments to collect data. The data had been collected from 50 out of 52 respondents which was withdrawn from a total of 60 element population by using simple random sampling. The data collected is then evaluated by using Statistical Package for Social Science (SPSS) Version 23.0. Pearson correlation analysis, it was found that only two variables were found to have a significant relationship with health wellbeing which is physical workplace environment and organizational culture. The other two variables which are psychosocial work environment and work life balance had no significant relationship with health wellbeing. Multiple Regression analysis indicated that there is a significant relationship between organizational culture and health wellbeing. However, no significant relationship was found between psychosocial work environment, physical workplace environment and work life balance.